Association Between Drug Burden Index and Functional and Cognitive Function in Patients with Multimorbidity - Villalba-Moreno, Angela Ma; Alfaro-Lara, Eva Rocío; Rodríguez-Pérez, Aitana; Báñez-Toro, Daniel; Sánchez-Fidalgo, Susana; Pérez-Guerrero, Ma Concepción; Santos-Ramos, Bernardo; Nieto-Martín, Ma D. (Current Pharmaceutical Design, 2018)
Background: Anticholinergic and sedative drugs are associated with adverse events such as cognitive and functional impairment in elderly. The Drug Burden Index (DBI) is a measure of an individual's total exposure to anticholinergic and sedative drugs. Objetive: The study aimed to evaluate the association between the total DBI and cognitive and functional impairment in patients with multimorbidity. Setting: Patients with multimorbidity enrolled in the IMPACTO project. Methods: Cross-sectional observational study. Main outcome measure: The anticholinergic and sedative exposure was calculated using DBI. The Pfeiffer Test (PT) was used for cognitive status and the Barthel Index (BI) for functional status. Results: 336 patients were included (mean age 77.6 ± 8.7 years, 54.2% men and a mean of 11.5 ± 3.7 prescribed drugs). 180 patients (53.6%) exposed to anticholinergic and/or sedative drugs were identified. The median score obtained in PT was slightly higher in exposed patients (1 (IQR 0-2) and 2 (IQR 0-4), p = 0.082 in
Keywords: multimorbidity